Basic Studies for Continuous Production of L-Aspartic Acid by Immobilized Escherichia coli Cells - Tosa, Tetsuya (1974)
By using a column packed with immobilized Escherichia coli cells entrapped in a polyacrylamide gel lattice, conditions for continuous production of L-aspartic acid from ammonium fumarate were investigated. When a solution of 1 M ammonium fumarate (pH 8.5) containing 1 mM Mg(2+) was passed through the immobilized cell column at a flow rate of space velocity (SV) = 0.8 at 37 C, the highest rate of reaction was attained. From the column effluents, L-aspartic acid was obtained in good yield. The immobilized cell column was very stable.